Artificial antigen-presenting interfaces in the service of immunology - Platzman, Ilia; Janiesch, Jan-Willi; Matić, Jovana; Spatz, Joachim P. (Israel journal of chemistry, 2013)
While the beneficial impact of modifying and/or targeting T lymphocytes is becoming increasingly accepted in the treatment of different diseases, the road towards cell-based immunotherapy is still long and winding. Major challenges that remain include, amongst others, the guidance and exquisite regulation of immune processes ex vivo. In part, this is due to the difficulties of simulating ex vivo the intimate cellular interactions that occur between T cells and antigen-presenting cells (APCs). The fate of T cells is not solely regulated by the presence of certain molecules on the surface of APCs but also by their density and spatial distribution on the micro- and nanometric scale. Moreover, mechanical properties of APCs and force-dependent conformational changes during the formation of an immunological synapse (IS; a highly organized supramolecular complex at the T cellAPC interface), play a crucial role in T cell fate regulation. Various different technical means have been developed to create APC substitutes that are able to simulate ex vivo signals originating from naturally occurring APCs. Here, we review the performance of APC surrogates and discuss their contribution to understanding mechanisms underlying the ability of T cells to perform the “intelligent” mission of acquiring, processing and responding to environmental information.